Navigating Negotiation Dynamics: The Impact of Technological Innovations and Sociocultural Factors in Supply Chain and Financial Systems - Shah, Stuti; Khubchandani, Sania; Nagani, Purva; Sakaria, Anuchi; Chauhan, Rahul; Maseleno, Andino; Rizal Isnanto, R. (Dinasti Information and Technology, 2024)
This study investigates the impact of technological innovations and sociocultural factors on negotiation processes, specifically focusing on e-payment systems. Utilizing demographic analyses, the research examines how age, gender, and education influence familiarity, usage, and effectiveness of e-payment technologies. The findings reveal significant differences in e-payment usage based on age and gender, while education shows a trend in influencing usage patterns. This research underscores the importance of understanding these demographic factors for enhancing negotiation strategies through technology. Additionally, it emphasizes the need for tailored approaches in organizations to improve user satisfaction and negotiation outcomes. Future research should explore additional variables and the long-term effects of technology on negotiation practices, contributing to a more inclusive global marketplace.